Valdosta State College Commencement Program, June 3, 1960 - Valdosta State College (Valdosta State University, 1960)
Valdosta State College. Commencement Program, June 3, 1960. UA-22-04. Box 1, Folder 6. Valdosta State University Archives and Special Collections
Keywords: Commencement ceremonies--Georgia--Valdosta; Valdosta State College; Valdosta State College--Students; Programs (Publications); Valdosta (Ga.)